Current research trends on cognition, integrative complexity, and decision-making: a systematic literature review using activity theory and neuroscience - Molina, Isaac; Molina-Perez, Edmundo; Sobrino, Fernanda; Tellez-Rojas, Mario Arturo; Zamora-Maldonado, Hilda C.; Plaza-Ferreira, María; Orozco, Yessica; Espinoza-Juarez, Victor; Serra-Barragán, Luis; De Unanue, Adolfo (Frontiers in Psychology, 2023)
This paper presents a systematic literature review that follows the PRISMA and PICOS guidelines to analyze current research trends on cognition, integrative complexity (a cognitive feature focusing on information processing in a person's response rather than its quantity or quality), and decision-making from the perspectives of activity theory and neuroscience. The study examines 31 papers published between 2012 and 2022 and identifies six categories within activity theory: subjects, objects, rules, community, division of labor, and outcomes. Furthermore, the study investigates the relationship between decision-making outcomes and integrative complexity as a cognitive feature in various contexts. Additionally, content analysis on neuroscience (19 articles) and integrative complexity revealed significant research gaps, including understanding the nature of integrative complexity, challenges related to its measurement, and differentiation from other cognitive features. We also identify opportunities for investigating the brain's activity during decision-making in relation to integrative complexity. We identify the need for a more precise categorization of integrative complexity in studies of cognition, integrative complexity, and decision-making. We discuss implications of our analysis for understanding the cognitive nature of integrative complexity and the potential of neuroscience methods for studying this attribute.